(untitled) - Henson, Jim.; Lazer, David; (Producer); Patchett, Tom.; Tarses, Jay.; Kaufman, Kenneth; Juhl, Jerry; Mazzarino, Joseph; Henson, Brian; Baker, Martin G.; Oz, Frank; Hill, Tim; et al. (Culver City, CA, 2006)
Muppets from space: "The Muppets embark on a hilarious extra-terrestrial adventure in hopes of learning about Gonzos past and discover that Gonzos family members are aliens from a distant planet."--Container.
Muppets take Manhattan: "Broadway bound, the Muppets take Manhattan by storm in this magical musical about breaking into show business!"--Container.
Keywords: Juvenile drama; Muppets (Fictitious characters); Drama; Video recordings; Video recordings for the hearing impaired; Juvenile works; Comedy films; Video recordings for the hearing impaired; Childrens films; Childrens films; Drama; Feature films